Development Strategy for Fish Processing MSMEs in Kampar Regency (Case Study: Koto Mesjid Village) - Helmi, Medina Febrisa; Marantika, Abshor; Kasmawati, Kasmawati (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are widely recognized as key drivers of regional economic development, in line with Schumpeter's entrepreneurship theory and Porter's concept of competitive advantage. This study examines the development of fish processing MSMEs in Kampar Regency, one of the main catfish production centers in Indonesia. Using a qualitative approach, data were collected through interviews, observations, documentation, and questionnaires, then analyzed using the SWOT (Strengths, Weaknesses, Opportunities, Threats) method. The results show that MSMEs in Kampar have strengths such as abundant raw materials, a skilled local workforce, and government policy support. However, there are weaknesses such as limited technology, limited financial resources, and underdeveloped distribution channels. Opportunities arise from increasing consumer demand and export potential, while threats include price fluctuations and inter-regional competition. The recommended development strategy is the Strength–Opportunity (SO) approach, focusing on product diversification, human resource capacity building, institutional strengthening, and digital marketing adoption. These steps are expected to increase competitiveness, ensure sustainability, and strengthen the contribution of MSMEs to regional economic growth.